2022
DOI: 10.3389/fendo.2022.926971
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between blood ethylene oxide levels and obesity in the general population: NHANES 2013–2016

Abstract: BackgroundEthylene oxide (EO) has been shown to associate with increased cardiovascular risk. This study aimed to explore the relationship and its meditating factors between EO exposure and the major cardiovascular risk factor of obesity among the general adult population.MethodsCross-sectional data of 3,220 participants from National Health and Nutritional Examination Survey (NHANES) 2013–2016 were enrolled. Obesity was defined as body mass index (BMI) ≥30 kg/m2, and abdominal obesity was defined as waist cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Recent studies reported there exist the link between EO exposure and some metabolic disorders, of which abdominal obesity was demonstrated to be signi cant determinants of hepatic lipid metabolism and independently predict the development of NAFLD [28][29][30]. In the present study, high EO levels were found to negatively associate with the risk of NAFLD, which was similar with one study result of evaluating the effect of EO on obesity [17]. Compared with the other studies with NAFLD as the outcome, we adopt two widely con rmed liver indices to assess NAFLD, thereby ensuring the stability of the results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies reported there exist the link between EO exposure and some metabolic disorders, of which abdominal obesity was demonstrated to be signi cant determinants of hepatic lipid metabolism and independently predict the development of NAFLD [28][29][30]. In the present study, high EO levels were found to negatively associate with the risk of NAFLD, which was similar with one study result of evaluating the effect of EO on obesity [17]. Compared with the other studies with NAFLD as the outcome, we adopt two widely con rmed liver indices to assess NAFLD, thereby ensuring the stability of the results.…”
Section: Discussionsupporting
confidence: 89%
“…The underlying mechanisms were required to be identify in the future study.Hemoglobin adducts of EO (HbEO) produced by the reaction between EO and hemoglobin (Hb) is a sensitive and effective hematological marker to assess EO exposure [10,11].Current evidence which suggested, as a potential exogenous toxicant, EO can pose deteriorated effects in human health is not extensive. Although some epidemiological studies reported that exposure to EO was associated with increased risk of asthma, serum lipid, hypertension, diabetes, and cardiovascular diseases (CVD) [12][13][14][15][16], one recent cross-sectional study have found an inverse association of blood EO levels with obesity in adults [17]. Considering that obesity and hypertension, diabetes, and CVD are all important risk factors in contributing to the development of NAFLD, it is required to further evaluate the uncertain association between EO and NAFLD.…”
mentioning
confidence: 99%
“…Iokfai Cheang et al. ( 24 ) reported that elevated quartiles of HbEO were inversely associated with BMI, WC and obesity following full adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, reducing tobacco use can mitigate the risk of depression to some extent. Besides, several recent studies have found that high levels of HbEO are signi cantly associated with a high prevalence of diabetes, obesity, heart disease, hypertension, chronic obstructive pulmonary disease in the general population 19,20,22,[35][36] . Therefore the potential adverse effects of HbEO exposure should be of concern not only to occupationally exposed persons but also to the general population.…”
Section: Discussionmentioning
confidence: 99%